Case Reports on the Failure of Smoking Marijuana to Prevent Relapse to Use of Opiates in Adolescents/Young Adults With Opiate Use Disorder. (2021) - Jaffe, Steven L.
Abstract: Twenty-six adolescent/young adult patients with opioid use disorder smoked marijuana in an attempt to avoid relapse to opiate use. In each case, smoking marijuana increased cravings and urges for opiates and promoted opiate relapse. These clinical case reports show that smoking marijuana was not helpful as a harm reduction strategy to prevent return to opioids in young people with OUD.